Comparison of the application value of contrast-enhanced ultrasound and contrast-enhanced CT in puncture biopsy of peripheral pulmonary lesions - Wang, Gang; Zhang, Ji-cheng; Wang, Zhi-hua; Gou, Bo; Liu, Xiao-lin; Liu, Gang; Liu, Jian (Frontiers in Oncology, 2025)
ObjectiveThis study assesses the clinical utility of contrast - enhanced ultrasound (CEUS) in comparison to contrast - enhanced computed tomography (CECT) in the context of peripheral lung mass biopsy. The overarching objective is to establish robust clinical benchmarks that can guide evidence - based decision - making in the field of pulmonary interventional procedures.MethodsA comparison of 420 patients admitted to our hospital from January 2019 to December 2022 who underwent biopsy using two different guidance methods, including 196 cases in the CEUS-guided biopsy group and 224 cases in the CECT-guided biopsy group. The average number of pleural punctures, puncture time, satisfaction with the first puncture specimen, diagnostic accuracy and complication rate were compared between the two guidance methods.Results① Compared with the CECT group, the CEUS-guided group required fewer pleural punctures (2.5 vs. 4.1 times) and shorter puncture time (24 minutes vs. 42 minutes) on average, and the difference was statistically significant (P<0.001). ② In terms of complications, the incidence of pneumothorax (3.1% vs. 8%) was lower in the CEUS group, while the incidence of bleeding (1.5% vs. 3.1%) had no significant difference between the two groups ③ When the diameter of the lesion is <3 cm, the specimen satisfaction and diagnostic accuracy of the CEUS group are lower than those of the CECT group (71.0% vs. 88.3%, 64.5% vs. 86.7%). When the diameter of the lesion is (3 ~ 6cm), the specimen satisfaction and diagnostic accuracy of the CEUS group were higher than those of the CECT group (98.6% vs. 89.6%, 95.8% vs. 85.2%), and the above differences were statistically significant; but when the diameter of the lesion was >6cm, there was no significant difference in specimen satisfaction rate and diagnostic accuracy between the two guidance methods.ConclusionCEUS is better than CECT in reducing the number of punctures, shortening puncture time and reducing the incidence of pneumothorax, and is especially suitable for the diagnosis of medium-sized lesions. However, for lesions less than 3 cm in diameter, CECT demonstrated higher specimen satisfaction and diagnostic accuracy. This suggests that diagnostic performance can be optimized by selecting appropriate guidance techniques based on lesion size and risk of complications.